2009
DOI: 10.1007/s11606-009-1191-6
|View full text |Cite
|
Sign up to set email alerts
|

Medical Student Patient Experiences Before and After Duty Hour Regulation and Hospitalist Support

Abstract: With institutional and residency changes, junior medicine clerkship students had fewer opportunities for direct care of patients and encountered a different mix of patient diagnoses. Increasingly during their junior medicine clerkship, students may not have exposure to basic medical conditions, which may affect their ability to care for future patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…19 • Additionally, in another study, 20 key clinical faculty, identified by internal medicine program directors, reported concerns about the impact of duty hours regulations on aspects of medical student education in internal medicine. Fifty-two percent reported worsening in the medical students' levels of responsibility on inpatient teams, ability to follow patients throughout hospitalization, ability to develop working relationships with residents, and overall quality of education.…”
Section: Intheunitedstatesgraduatemedicalmentioning
confidence: 99%
See 1 more Smart Citation
“…19 • Additionally, in another study, 20 key clinical faculty, identified by internal medicine program directors, reported concerns about the impact of duty hours regulations on aspects of medical student education in internal medicine. Fifty-two percent reported worsening in the medical students' levels of responsibility on inpatient teams, ability to follow patients throughout hospitalization, ability to develop working relationships with residents, and overall quality of education.…”
Section: Intheunitedstatesgraduatemedicalmentioning
confidence: 99%
“…Fifty-two percent reported worsening in the medical students' levels of responsibility on inpatient teams, ability to follow patients throughout hospitalization, ability to develop working relationships with residents, and overall quality of education. 19 • Also, authors of another study surveyed students about their perceptions of the quality of their experiences in four required clerkships before and after duty hours regulations. 21 In the surgical clerkships (surgery and obstetrics-gynecology), students noted a decrease in the accessibility of residents, a decrease in the quality of their teaching and feedback, and a decrease in the overall quality of the clerkship.…”
Section: Intheunitedstatesgraduatemedicalmentioning
confidence: 99%
“…Based on this feedback, caution should be taken in assigning more junior students to uncovered hospitalist services. This is especially true in the post‐duty hour setting which has already prompted concern related to student exposure to basic medical conditions 13…”
Section: Discussionmentioning
confidence: 99%
“…Duty-hour regulations have resulted in faculty and residents perceiving less time to teach students, reduced continuity of patient care, and decreased volume and variety of patient exposures for students. [8][9][10][11][12][13] Billing and medico-legal concerns have resulted in many institutions prohibiting students from using EHRs. 14 Medicine (APDIM) surveyed its members about the IM subinternship.…”
mentioning
confidence: 99%